2020
DOI: 10.1016/j.scitotenv.2019.134774
|View full text |Cite
|
Sign up to set email alerts
|

Wheat is an emerging exposure route for arsenic in Bihar, India

Abstract: In arsenic (As) endemic areas of southeast Asia, where a subsistence rice-based diet is prevalent, As exposure from food is mainly focused on rice intake. However, consumption of wheat is substantial and increasing. We present a probabilistic assessment of increased cancer risk from wheat-based food intake in a study population of rural Bihar, India where As exposure is endemic. Total As in wheat grains (43.64±48.19 µg/kg, n=72) collected from 77 households across 19 villages was found to be lower than reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Most recently, it has been reported that 22 districts of Bihar are currently As-impacted, although no further details such as location, non-summarized data or the functional definition of "As-impacted" are included [78]. Further, wheat consumption has recently been identified as an emerging route of As exposure in Bihar [84]. Although thorough reviews of the status of As in the Gangetic Basin are published elsewhere [78,85], the estimated population at risk for As contamination in West Bengal is 26 million people, followed by Bihar (9 million), Uttar Pradesh (3 million), Assam (1.2 million), Manipur (1 million) and Jharkhand (0.4 million) [85].…”
mentioning
confidence: 99%
“…Most recently, it has been reported that 22 districts of Bihar are currently As-impacted, although no further details such as location, non-summarized data or the functional definition of "As-impacted" are included [78]. Further, wheat consumption has recently been identified as an emerging route of As exposure in Bihar [84]. Although thorough reviews of the status of As in the Gangetic Basin are published elsewhere [78,85], the estimated population at risk for As contamination in West Bengal is 26 million people, followed by Bihar (9 million), Uttar Pradesh (3 million), Assam (1.2 million), Manipur (1 million) and Jharkhand (0.4 million) [85].…”
mentioning
confidence: 99%
“…Further, younger cancer patients may face life disruptions (Clark & Fasciano 2015;Nass et al 2015) such as career/education, future plans, trust in health, financial burdens, peer relationships, and family dynamics. In addition, their geographical establishment could be held responsible, since most of the inhabitants of arsenic-affected middle Gangetic plain of Bihar, for obvious reasons, could not relocate (Bhardwaj et al 2019) and as such are bound to live under continuous apprehension for their next generations, highly vulnerable to several arsenic-induced diseases (Laskar et al 2010;Syed et al 2012;Thakur & Gupta 2015;Suman et al 2020). Most of the AIC patients of the age group 32-40 years were literate (63.63%).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prominent biomarkers were used to confirm that the patient is suffering from cancer due only to high exposure to arsenic through drinking water. Their differential diagnosis for arsenicinduced cancer was made by the researchers at MCSRC based on respective clinical history for presence of arsenicosis and absence of any clinical co-morbidity (Kumar & Ghosh 2019;Kumar et al 2020Kumar et al , 2021Kumar et al , 2022.…”
Section: Research Design Study Area and Samplementioning
confidence: 99%
“…As a result, wheat and wheat-based products are major dietary sources of Cd ( Greger and Löfstedt, 2004 ; Punshon and Jackson, 2018 ). Although wheat grain has lesser As accumulation than rice ( Williams et al., 2007 ; Bhattacharya et al., 2010 ; Saeed et al., 2021 ), high As concentration was commonly detected in the grain of wheat grown in As-contaminated soils ( Duncan et al., 2017 ; Suman et al., 2020 ). Arsenic is typically present in wheat grain in an inorganic form ( Zhao et al., 2010 ; Shi et al., 2013 ; Rasheed et al., 2018 ), which is more toxic to humans than the organic form ( Styblo et al., 2000 ; Sun et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%